Dampak input (tenaga kerja) dan output (GDP) sektor pertanian terhadap konsumsi pemerintah di Indonesia - Nurjanah, Rahma; Achmad, Erni (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
This study aims to analyze the development of inputs (labor) and output (GDP) in the agricultural sector and government consumption in Indonesia during the period 1993-2014 and analyze the impact of inputs (labor) and output (GDP) on the agricultural sector on government consumption in Indonesia. The result of the research show during period from 1993-2014 output GDP in agriculture sector is 17% with an average value is 496,9 trillion rupiah. For agricultural sector workers the average value of growth is equal to -0.007%, with an average value of 39,621.18 thousand people, the highest growth occurred in 1998 which amounted to 13.29% and the lowest growth occurred in 1997 which was equal to -7.76%. The regression results show that the GDP variable Output of the agricultural sector has a positive and significant effect on government consumption, while the agricultural sector labor variable has no significant effect on government consumption.